Chemical and biological methods for color removal from wastewater of carton-printing ink industry / Selasiah Wahab - Wahab, Selasiah (2008)
Water-based and solvent-based ink wastewaters from carton-printing industry are generated from the cleaning of printing machines when the color of the printing ink is changed. Generally, the wastewater is intense in color and high in composition of organic compounds. Colors are recalcitrant compounds and solvents are toxic to microorganism; they often cause the conventional treatment plant to become ineffective. In this study the removal of color and COD was attained by using individual chemical and biological first, and subsequently two combined chemical and biological methods (I & II) for water-based and solvent-based printing ink wastewaters. The chemical methods include coagulation and flocculation, Fenton and Fenton-like reagent. The biological method was carried out with two white rot fungi, namely Coriolus versicolor and D-UiTM. Biological treatment using C. versicolor in the growth medium M1 shows higher removal of color and COD compared to growth medium M2. For water-based printing ink wastewater, it is found that combined method I of Fenton reagent followed by biological method is as with M1 effective as combined method II, both being able to reduce the color and COD to below the standard discharge limits of DOE. However, combined method I is more efficient than combined method II in term of hydraulic retention time being one day as compared to 4 days for method II. For solvent-based printing ink wastewater both combined methods are equally efficient to archive more than 90% removal of color and COD with the same hydraulic retention time. But, combined method I resulted in lower values of color and COD in the final treated water. The results obtained indicate that the effectiveness of individual chemical and biological methods is less than that the combined methods.